The Developing of a Diabetic Retinopathy Screening Program (Eye 3 MUST), Narathiwas Rajanagarindra Hospital - Kuiburd, Thussaneeya; Pumiapiradee, Wantanee; Wannasakol, Onanong; Masa, Yamilah; Nawsuwan, Kittiporn; Wansawat, Tidarat (Princess of Naradhiwas University Journal, 2025)
The objectives of this research and development were to assess screening prevalence of diabetic retinopathy, and create and evaluate the diabetic retinopathy screening model (eyes 3 must). The processes of this study were conducted in 3 phases: 1) examine the diabetic retinopathy screening status of thirty patients with diabetes mellitus and seven medical professionals, including physicians and nurses. The data was gathered through focus group discussions. Content analysis was used to analyze the data; 2) three experts reviewed the draft of the diabetic retinopathy screening model and 27 registered nurses evaluated its appropriateness, feasibility, and benefits for service clients; and 3) a quasi-experimental methodology of a one-group prepost test with 99 patients with diabetes mellitus was used to assess the model’s efficacy. The instruments used in this study were developed diabetic retinopathy screening model and screening record form. Data was analyzed by using frequency, percentage, and one sample t-test. According to the study’s findings, the referral process for eye screenings was confusing, there were not enough nurses to handle every case, and patients denied eye examination because of lengthy wait times. The diabetic retinopathy screening model (eyes 3 must) consisted of: 1) preparation before the procedure (must prepare); 2) prompt examination on the day of the procedure (must examine quickly; and 3) follow-up after the procedure (must follow up). According to the results after using the diabetic retinopathy screening model, the screening rate increased from 54.17 percent in 2022 to 71.36 percent in 2023 and 63.03 percent in 2024, respectively. Following the implementation of the diabetic retinopathy screening model, the rate of complications from diabetic retinopathy dropped from 7.37 percent in 2023 to 7.25 percent in 2024. Following the model’s implementation, the waiting time for eye examination decreased from 28 minutes to 15.36 minutes (S.D. = 0.63), which was statistically substantially less than the hospital’s usual time setting of 20 minutes at the.001 level (t = 73.21).